2021
DOI: 10.37394/23207.2021.18.12
|View full text |Cite
|
Sign up to set email alerts
|

Management of the Tourist Region - Identification of the determinants of Innovation

Abstract: The objective of this paper is to identify the entities responsible for creating the environment of aninnovative tourism region and to identify the activities that create it. The expert method was used in the paper.Pilot studies were conducted in November 2017, basic studies were conducted in May and June 2018, as well asin June 2019. The research tool was a questionnaire. The CAWI technique was used. The results were subject tostatistical calculations. The empirical results show that four categories of factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 46 publications
(108 reference statements)
0
1
0
Order By: Relevance
“…The accommodation sector is dominated by environmental and process innovations, while the leisure and entertainment attractions sector is dominated by structural and social innovations, according to Booyens and Rogerson [10]. Expert research on the designation of tourist entities responsible for stimulating the innovation of the tourist region showed that the greatest impact on the innovation of the tourist region is attributed to amusement parks, having the greatest impact on creating an offer for which there are no substitutes [47]. From the tourist's point of view, companies in the recreational industry are an optional good or even a luxury [23]; thus, only their high creativity can attract a client [48].…”
Section: Innovations In the Tourism Sectormentioning
confidence: 99%
“…The accommodation sector is dominated by environmental and process innovations, while the leisure and entertainment attractions sector is dominated by structural and social innovations, according to Booyens and Rogerson [10]. Expert research on the designation of tourist entities responsible for stimulating the innovation of the tourist region showed that the greatest impact on the innovation of the tourist region is attributed to amusement parks, having the greatest impact on creating an offer for which there are no substitutes [47]. From the tourist's point of view, companies in the recreational industry are an optional good or even a luxury [23]; thus, only their high creativity can attract a client [48].…”
Section: Innovations In the Tourism Sectormentioning
confidence: 99%